Peran Layanan Konseling Individu Dalam Meningkatkan Motivasi Belajar Siswa Di SMP PPM Tana Toraja - Nasyith Nabilun Zayyaf (CV. ITTC INDONESIA, 2026)
Individual counseling service plays a strategic role in improving students' learning motivation, particularly within pesantren-based educational environments where students face unique challenges such as densely structured schedules and dormitory life. This study aims to describe the implementation of individual counseling services and identify supporting and inhibiting factors affecting its effectiveness in increasing students' learning motivation at UPT SMP Pesantren Pembangunan Muhammadiyah Tana Toraja. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with the guidance and counseling teacher and five students, complemented by observation and documentation. Data analysis followed the interactive model of Miles and Huberman: data reduction, data display, and conclusion drawing, with validity verified through source and technique triangulation. Results indicate that individual counseling services—conducted through empathic, one-on-one interviews—significantly helped students recognize their learning barriers, develop self-awareness, and gradually build intrinsic learning motivation. Supporting factors included students' readiness to change, an empathic counselor–student relationship, and the disciplined environment of the pesantren. Inhibiting factors included students' physical and mental fatigue caused by packed daily schedules, students' reluctance to disclose problems, and the absence of a systematic scheduling and recording system for individual counseling sessions. The study concludes that individual counseling has significant potential to improve learning motivation when implemented systematically and responsively to student needs.